Novograblenovite from Radlin, Upper Silesia, Poland and its relation to 'redikortsevite'. (5th April 2021) - Parafiniuk, Jan; Stachowicz, Marcin; Woźniak, Krzysztof
Abstract: The paper presents detailed mineralogical and structural characteristics of novograblenovite that occurs abundantly on a burning coal dump at Radlin, Upper Silesia, Poland. Our results indicate that NH4 MgCl3 ⋅6H2 O is the proper formula of this mineral. The thermal behaviour of novograblenovite shows a two-step dehydration at 155 and 193°C and sublimation of NH4 Cl at 341°C. A Raman spectrum, obtained for the first time, reveals the normal modes of H2 O and NH4 + vibrations. The crystal structure of novograblenovite was refined on the basis of high quality X-ray diffraction data. The final discrepancy factor w R 2 was 0.0567 for 94 parameters and 1464 independent reflections. The structure has a monoclinic C 2/ c space group symmetry with the following unit cell parameters: a = 9.2709(3) Å, b = 9.5361(2) Å, c = 13.2741(4) Å and β = 90.054(3)°. We were able to specify the architecture of the disordered NH4 + cation located at the symmetry centre. This led to reasonable parameters for the H-bonding formed by this cation. In carnallite the K + cations occupy an identical space to the ammonium ion in novograblenovite, but when embedded into the latter crystal structure it is bound less tightly. Voids occupy 14% of the space in the novograblenovite crystal structure. Novograblenovite is exactly the same phase as the 'redikortsevite' described previously from Chelabinsk coal dumps and this informally introduced name should be abandoned.